Vascular cells respond differentially to transforming growth factors beta 1 and beta 2 in vitro. - Merwin, J. R. (1991)
Transforming growth factor beta 1 (TGF-beta 1) and beta 2 (TGF-beta 2) are equipotent in many cell systems studies thus far. Recent data, however, show different effects elicited by these two growth factors in specific biologic systems. This investigation compares the effects of TGF-beta 1 and TGF-beta 2 bovine aortic endothelial cells (BAECs), rat epididymal fat pad microvascular endothelium (RFCs), and bovine aortic smooth muscle cells (BASCs). In two-dimensional cultures, proliferation of BAECs, BASMCs, and RFCs were all inhibited by TGF-beta 1, while in response to TGF-beta 2, BASMCs were fully inhibited, RFCs were modestly inhibited, and BAECs were unaffected. Bovine aortic endothelial cell migration was significantly inhibited by TGF-beta 1, but only slightly inhibited by TGF-beta 2. In contrast, BASMC migration was enhanced by TGF-beta 1 and was not affected by TGF-beta 2. In three-dimensional cultures, RFCs were stimulated to undergo in vitro angiogenesis in response to TGF-beta 1 and TGF-beta 2 at 10-fold higher concentrations. Three distinct receptor assays demonstrated the presence of type I and type II TGF-beta 1 cell-surface-binding proteins on BAECs, BASMCs, and RFCs. Labeled TGF-beta 1 was competed off completely with 100-fold molar excess unlabeled TGF-beta 1, but only partially with equivalent excess unlabeled TGF-beta 2. Furthermore the ratios of type I to type II TGF-beta receptors in these three vascular cell types vary from 1:1 in BAECs to 1.5:1 in RFCs to 3:1 in BASMCs and can be correlated with the differences noted in cellular responses to TGF-beta 1 and TGF-beta 2 in proliferation, migration, and in vitro angiogenic assays. These findings support the hypothesis that there are different responses to the TGF-beta s, depending on the cell type and experimental conditions as well as the TGF-beta concentration and isoform used.